1992
DOI: 10.1002/art.1780350715
|View full text |Cite
|
Sign up to set email alerts
|

Type x collagen synthesis in human osteoarthritic cartilage. indication of chondrocyte hypertrophy

Abstract: Objective. To investigate the appearance of hypertrophic chondrocytes in osteoarthritic (OAj cartilage, using type X collagen as a specific marker.Methods. The biosynthesis of type X collagen was examined by metabolic labeling of freshly isolated articular chondrocytes with 3H-proline, immunoprecipitation, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the synthesized collagens. Extracellular deposition of types X and I1 collagen was analyzed immunohistochemically . Chondrocytes of normal adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
256
2
9

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(282 citation statements)
references
References 16 publications
15
256
2
9
Order By: Relevance
“…It has also been 416 STOKES ET AL shown that chondrocytes within the deep zones of OA cartilage can express type X collagen, indicating that they may be undergoing hypertrophy (8,9,72,73). Others have observed the synthesis by OA chondrocytes of aggrecan molecules that resemble the structure of aggrecan molecules in fetal chondrocytes (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been 416 STOKES ET AL shown that chondrocytes within the deep zones of OA cartilage can express type X collagen, indicating that they may be undergoing hypertrophy (8,9,72,73). Others have observed the synthesis by OA chondrocytes of aggrecan molecules that resemble the structure of aggrecan molecules in fetal chondrocytes (11).…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the biosynthetic profile of dedifferentiated chondrocytes resemble some of the phenotypic changes displayed by OA chondrocytes, and the matrix they produce is similar to that synthesized by chondroprogenitor cells (7)(8)(9)(10)(11)(12)(13)17,(37)(38)(39)(40). However, the mechanisms responsible for the phenotypic instability of chondrocytes and the regulation of these different chondrocyte-specific phenotypes remain poorly understood.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…It is expressed by hypertrophic chondrocytes in the calcifying zone of the growth plate [1,6], in zones of secondary ossification [ 11, in newly forming osteophytic or reparative cartilage [7,8], or in bone callus during fracture healing [9]. This restricted expression to zones of degrading cartilage implies that collagen type X may play an important role in the regulation of endochondral ossification and cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently published studies on the developmental expression in fetal cartilage, in adult h&thy, as well as in osteoarthritic and rheumatoid adult cartilage [1, 7,8] indicating precisely regulated gene activation. Changes of in vitro expression patterns of type X collagen due to the influences of retinoic acid [24], of vitamin D [25] and of calcium j?-glycerophosphate [26] also suggest a precise and highly complex ,regulation of the expression of its gene.…”
Section: Introductionmentioning
confidence: 99%